International comparative study of medical service at Antarctic wintering-over stations - Yasuhisa Hasegawa; Kentaro Watanabe (Antarctic Record, 2007)
In October, 2005, we sent several questions to foreign Antarctic wintering-over stations by e-mail, and made an international comparative study of winter medical services at 18 stations of 13 nations. The number of wintering members at the stations that we investigated was 4-37 persons, and the average age was 36.4 years old. Syowa Station had two medical doctors, and the others had one each. There were 4 female doctors, 22% of all wintering-over doctors. About 60% stations had medical facilities for operations under general-anesthesia. In the past, 32 operations including 14 appendectomies have been performed at 9 stations. There have been 18 deaths at 9 stations. Most were accidental deaths, 2 were caused by acute myocardial infarction. At 11 stations, there were 21 medical evacuations in summer, and 2 in winter, including 11 cases of orthopedic disease and 3 of acute appendicitis.